Vitamin D supplementation to the older adult population in Germany has the cost-saving potential of preventing almost 30,000 cancer deaths per year - Niedermaier, Tobias; Gredner, Thomas; Kuznia, Sabine; Schöttker, Ben; Mons, Ute; Brenner, Hermann (Molecular oncology, 2021)
Recent meta-analyses of randomized controlled trials (RCTs) have demonstrated significant reduction of cancer mortality by vitamin D supplementation. We estimated costs and savings for preventing cancer deaths by vitamin D supplementation of the population aged 50+ years in Germany. Our analysis is based on national data on cancer mortality in 2016. The number of preventable cancer deaths was estimated by multiplying cancer deaths above age 50 with the estimated proportionate reduction of cancer mortality derived by vitamin D supplementation according to meta-analyses of RCTs (13%). Saved costs were estimated by multiplying this number by estimated end-of-life cancer care costs (€40,000). Annual costs of vitamin D supplementation were estimated at 25€ per person above age 50. Comprehensive sensitivity analyses were conducted. In the main analysis, vitamin D supplementation was estimated to prevent almost 30,000 cancer deaths per year at approximate costs of €900 million and savings of €1.154 billion, suggesting net savings of €254 million. Our results support promotion of supplementation of vitamin D among older adults as a cost saving approach to substantially reduce cancer mortality.
Gesehen am 12.02.2021